Test and Analysis of Three Directional Vibration for Harmonic Reducer - Tan Jing; Shi Deyu; Huang Dishan; Gu Jingjun (Jixie chuandong)
A new vibration testing method is introduced to measure three directional vibration of the harmonic reducer used in industrial robot. To simulate the working state of industrial robot,the harmonic reducer loading device is designed. In the case of loading,the vibration of a harmonic reducer in three direction is measured. The time domain statistics and frequency domain analysis are carried out for the measured data. The experimental data is used to evaluate the vibration performance,analyze the vibration characteristics of the harmonic reducer,and determine the cause of the vibration abnormality. The research results show that the presented measuring method is helpful to monitor the vibration performance of the harmonic reducer,and control the quality of the product.